Air pollution problems in an Indian opencast coal mining complex: A case study - Dhar B.B.; Jamal A.; Jamal R. (My University, 2025)
The air quality survey in an opencast (openpit) coal mining complex has revealed that the problem of air pollution is significant in the mining area. However, in comparison to SO, and NO, SPM levels were found to be the major threat to the air quality, and therefore calls for immediate mitigation measures. However it has been assessed that proper management at the planning stage could have reduced the concentration levels of pollutants, had it been due consideration at that stage of development. This aspect of course is in addition to meteorological parameters that often play a significant role in deciding the environmentally safe residential areas in such complexes. The need of the hour for bigger complexes, therefore is, a proper baseline data and the development of an integrated approach at the planning stages itself, if meaningful results have to be obtained. This case study is a step in that direction to help the planners to take necessary precautions in improving the air quality in an around a mining complex. © 1991, Taylor & Francis Group, LLC. All rights reserved.